2014
DOI: 10.1002/2014ja019864
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the loss of inner belt protons by magnetic field line curvature scattering

Abstract: The sudden loss of energetic protons in the inner radiation belt has been observed during geomagnetic storms. It is hypothesized that this sudden loss occurs because of changes in the geomagnetic field configuration which lead to a breakdown of the first adiabatic invariant, μ, in a process called magnetic field line curvature scattering or μ scattering. Comparison of observations to various analytic model predictions for μ scattering induced loss has, however, yielded discrepancies. To better understand how w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…However, we do not discuss the proton radiation belt since we do not have contributions on this subject in this Special Collection. More information on the proton belt can be found in, for example, Spjeldvik (), Beutier et al (), Albert et al (), Looper et al (), Selesnick, Looper, and Mewaldt (), Ginet et al (), Selesnick, Hudson, and Kress (), Selesnick et al (, , ), Mazur et al (, ), Tu, Cowee, and Liu (), and Borovsky et al (). In addition, we do not discuss any kind of trapped particles that originate from the nuclear reaction of ultrahigh energy proton (e.g., Gusev, Kohno et al, ; Gusev, Martin et al, ; Pugacheva et al, ; Selesnick, Looper, Mewaldt, & Labrador, ), suprathermal ionospheric heavy ions (e.g., Spjeldvik, ) such as iron ions (Christon et al, ; Spjeldvik et al, ) or carbon ions (Spjeldvik, ), high‐energy solar protons (e.g., O'Brien et al, ), or cosmic rays (e.g., Amato & Blasi, ; Blake et al, ; Smart et al, ; Shea et al, ; Smart & Shea, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not discuss the proton radiation belt since we do not have contributions on this subject in this Special Collection. More information on the proton belt can be found in, for example, Spjeldvik (), Beutier et al (), Albert et al (), Looper et al (), Selesnick, Looper, and Mewaldt (), Ginet et al (), Selesnick, Hudson, and Kress (), Selesnick et al (, , ), Mazur et al (, ), Tu, Cowee, and Liu (), and Borovsky et al (). In addition, we do not discuss any kind of trapped particles that originate from the nuclear reaction of ultrahigh energy proton (e.g., Gusev, Kohno et al, ; Gusev, Martin et al, ; Pugacheva et al, ; Selesnick, Looper, Mewaldt, & Labrador, ), suprathermal ionospheric heavy ions (e.g., Spjeldvik, ) such as iron ions (Christon et al, ; Spjeldvik et al, ) or carbon ions (Spjeldvik, ), high‐energy solar protons (e.g., O'Brien et al, ), or cosmic rays (e.g., Amato & Blasi, ; Blake et al, ; Smart et al, ; Shea et al, ; Smart & Shea, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work [ Hudson et al , ; Young et al , ; Tu et al , ] has suggested that proton loss from the outer edge of the inner radiation belt is due to field line curvature scattering (FCS). For this reason we have run all of our simulations using the Lorentz force equation, so that the gyromotion of the particles is accurately modeled.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we focus on loss events. Several mechanisms for inner ion belt losses during storms have been theorized including the following: hydromagnetic waves [Dragt, 1961], low-frequency magnetic fluctuations [McIlwain, 1965], perturbation of the boundary of the inner zone [Gussenhoven et al, 1994], and breakdown of adiabatic motion of protons due to magnetic field disturbances [Anderson et al, 1997;Young et al, 2002;Tu et al, 2014]. Because the loss event studied in this paper is correlated to the minimum Dst of an accompanying geomagnetic storm, we attribute it to the breakdown of adiabatic motion and subsequent field line curvature scattering (FCS).…”
Section: Introductionmentioning
confidence: 99%